PENINGKATAN PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN MODEL PROLEM BASED LEARNING DI SEKOLAH DASAR - Lusiana, Lusiana; Arwin, Arwin; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is aimed to describe the improvement of student learning outcomes on integrated thematic learning using Problem Based Learning (PBL) model. The type of research is Classroom Action Research with qualitative and quantitative approach. The research was conducted in the first semester of academic year 2018/2019. The research subjects were teachers and students, the number of students was 18 people. The research data obtained from observation, a test, and untest. The research procedure is planning, execution, observation, and reflection. Result of research from RPP I average value 85,23% (B), cycle II average value 97,73% (SB). The teacher cycle I aspect averages 82,82% (B), cycle II the average value of 96,88% (SB). Student Aspects of the first cycle of the average score of 81,25% (B), cycle II the average value of 96,88% (SB). Result of learning cycle I average value of 72,78, cycle II mean value 86,94. Concluded Problem Based Learning (PBL) model can improve student learning outcomes. Keywords: integrated thematic learning, Problem Based Learning.